PENERAPAN MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN KERJA ILMIAH SISWA MTS BABUSSALAM PENIRAMAN - Heni Erliani; Husna Amalya Melati; Rahmat Rasmawan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to describe the students’ scientific work skills before and after implementing the guided inquiry model and determine whether there are differences in the scientific work skills of students on environmental pollution material. This is a pre-experimental study on seven grade students of Madrasah Tsanawiyah (MTs) Babussalam Peniraman, of which 27 students took part as the research subjects. Data collection tools used were scientific work skills tests, observation sheets, and interview guidelines, while the Wilcoxon test was used to analyze scientific work skills before and after the guided inquiry model was applied. Analysis results of students’ scientific work before applying the learning model were in the less skilled category by 32% and unskilled by 68%. Meanwhile, the analysis results of the skills after implementing the guided inquiry model were in the highly-skilled, skilled and less skilled categories 33.3%, 29.2%, and 37.5% respectively. Wilcoxon test results showed that the value of Asymp. Sig. (2-tailed) was 0,000, which means less than 0.05 (<0.05). In conclusion, there are differences in the scientific work skills of seven grade students of MTs Babussalam Peniraman in learning environmental pollution material before and after the guided inquiry model was applied.Keywords:   Guided Inquiry, Scientific Work Skills, and Environmental Pollution